الآثار الاجتماعية لسياسة التحرير الاقتصادى - حبة، هاجر علي محمد بخيت (هيئة علماء السودان, 2010)
In this study, the researcher investigates the social impacts of free economy policy. \ The basic hypothesis is that the application of restructuring policy in Sudan entails social impacts that had, negatively, influenced the social fabric as a whole. \ The study includes setting the frame of free Economy policy, foreign Debt conditions related to the monitory fund and the National Bank, and I he aims of restructuring policies in Sudan. \ The results are important and assured basic and sub-hypotheses. The most important of these results are the following:- \ 1-\ Free Pricing System Policy,% the Reduction of wages real value, cancelling of services and commodity support, setting indirect taxes led to high increase of poverty level for the majority of citizens. This situation brought benefits to great tradesmen . \ 2-\ Privatization of institutes &firms increased rate of unemployment. \ 3-\ Un employing graduates in civil service increased unemployment among university graduates. \ 4-\ Giving the whole chance for foreign labour reduced chances for home labour. \ 5-\ Shortage\ of income led to the diminishing of food, hygiene . education and living status. \ 6-\ Excessive \ crime and drugs among young esters , and the emergence of behavioral problems and negative convictions had influenced the Sudanese social fabric . \ 7-\ The negative impact of the immigration of scholars who have wide experience. \ 8-\ Free Foreign Trade entails the cancelling of supporting young traders and many domestic factories stop working.
تناولت الباحثة في هذه الدراسة الآثار الاجتماعية لسياسة التحرير الاقتصادي، انطلقت هذه الدراسة من افتراض أساس هو أن تطبيق سياسة إعادة الهيكلة في السودان ترتبت عليه آثارا اجتماعية أثرت سلبا على النسيج الاجتماعي السوداني بجميع مكوناته. وقد اشتملت الدراسة على تحديد مفهوم سياسة التحرير الاقتصادي، شروط المديونية الخارجية من صندوق النقد والبنك الدولي. أهداف سياسات التكيف الهيكلي، ثم الآثار الاجتماعية لسياسة التحرير الاقتصادي في السودان. وتوصلت الباحثة إلى نتائج هامة أكدت فرضية الدراسة الأساسية والفروض الفرعية، وأهم هذه النتائج: \ 1.\ سياسة تحرير الأسعار وتخفيض القيمة الحقيقية للأجور وإلغاء الدعم من السلع والخدمات وفرض الضرائب غير المباشرة أدت إلى زيادة الفقر بالنسبة لغالبية المواطنين. واستفاد من هذا الوضع كبار التجار. \ 2.\ سياسة خصخصة المؤسسات زادت من نسبة البطالة بنسبة كبيرة. \ 3.\ إيقاف التعيينات الوظيفية أدت إلى المزيد من البطالة خاصة وسط خريجي الجامعات. \ 4.\ فتح الباب على مصراعيه للعمالة الأجنبية زاد من ضيق فرص العمل للعمالة المحلية. \ 5.\ انخفاض أو عدم وجود مصادر للدخل أدى إلى تدني في المستوى الغذائي والصحي والتعليمي والبيئة السكنية لشريحة كبيرة من المجتمع. \ 6.\ انتشار الجريمة العلمية والمخدرات وسط الشباب وظهور مشاكل سلوكية وأخلاقية وظواهر سالبة أثرت على النسيج الاجتماعي للمجتمع السوداني. \ 7.\ هجرة الكثير من العقول المبدعة إلى خارج السودان وإهدار خبرات قيمة. \ 8.\ تحرير التجارة الخارجية ترتب عليه تراجع عن حماية صغار المنتجين وتوقف الكثير من المصانع المحلية عن الإنتاج.
Keywords: سياسة التحرير الاقتصادى فى السودان -- شروط المديونية الخارجية -- سياسات التكيف الهيكلى